Thermal stress analysis of electronic packaging components - See Toh, Chee Wai. (2008)
The stress and strain behaviour of surface-mounted electronic packaging components under temperature cycling fatigue and creep deformations was investigated by non-linear three dimensional finite element method. In this research, solder joints of a PQFP package with a corner lead and solder joints of a CBGA package were studied.